2015
DOI: 10.1002/app.42144
|View full text |Cite
|
Sign up to set email alerts
|

Carboxymethylcellulose (CMC) as a model compound of cellulose fibers and polyamideamine epichlorohydrin (PAE)–CMC interactions as a model of PAE–fibers interactions of PAE‐based wet strength papers

Abstract: Carboxymethylcellulose (CMC) is a cellulose derivative obtained by the carboxymethylation of some hydroxyl groups in the cellulose macromolecules. In this article, we use CMC as a model compound of cellulose fibers to study polyamineamide epichlorohydrin (PAE)-fibers interactions during the preparation of PAE-based wet strength papers. The main advantages of the use of CMC to replace cellulose fibers are its water-soluble character and the homogeneous reaction medium during mixing with PAE resin. Based on 13 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…In the review by Espy (1995) it is stated that alcohol groups may play a part in cross-linking reactions as well as carboxylate end groups of cellulosic polymers. Other reports of the chlorohydrin-azetidinium salts reactivity in PAE are that carboxymetylated cellulose (CMC) or other carboxyl-bearing polymers showed an increased effectiveness in reaction with PAE (Siqueira et al 2015). Also, Obokata and Isogai (2007) have commented in their study on PAE that TEMPO-oxidized cellulose under alkaline conditions showed an increased reactivity toward PAE resulting in increased wet strength in cellulose sheets.…”
Section: Introductionmentioning
confidence: 99%
“…In the review by Espy (1995) it is stated that alcohol groups may play a part in cross-linking reactions as well as carboxylate end groups of cellulosic polymers. Other reports of the chlorohydrin-azetidinium salts reactivity in PAE are that carboxymetylated cellulose (CMC) or other carboxyl-bearing polymers showed an increased effectiveness in reaction with PAE (Siqueira et al 2015). Also, Obokata and Isogai (2007) have commented in their study on PAE that TEMPO-oxidized cellulose under alkaline conditions showed an increased reactivity toward PAE resulting in increased wet strength in cellulose sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Reagents that react with the sulfate groups of polysaccharides are less explored; however, they may be useful and may have an impact in biological, medicinal, and material applications. From previous research, it is known that azetidinium salts react preferentially with carboxylates, amines, phenols, and phosphorus nucleophiles . Azetidinium salts are positively charged, which to some extent governs their adsorption to carboxylic acids via electrostatic interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The EA results of AN, NVF, CMC, and the new flocculant (CMC-g-PAMD) were given in Table 1. It was apparent from the table that the C, H, O and N contents of the bands at 3262 and 1382 cm -1 were corresponding to N-H and C-N stretching vibration peaks in amide group respectively, and a stretching vibration peak of C=O appeared at 1669 cm -1 (31). For the AN spectrum in Figure 2b, the peak at 2228 cm -1 (AN) confirmed the existence of C≡N (32).…”
Section: Eamentioning
confidence: 83%